Jawabanmu

2014-08-11T20:39:01+07:00
Jika f(x) dibagi oleh x² - 4 sisanya x + 23 .
x² - 4 = (x+2)(x-2) -------> x = 2 atau x= -2

f(2) = 2 + 23
       = 25

f(-2) = -2 + 23
        = 21

untuk x = 2

2x³+ax²-bx+3 = 25
2(2)³ + a(2²) - 2b + 3 = 25
16 + 4a - 2b + 3 = 25
4a - 2b = 6
2a - b = 3

untuk x = -2

2x³+ax²-bx+3 = 21
2(-2)³ + a(-2²) + 2b + 3 = 21
-16 + 4a + 2b + 3 = 21
4a + 2b = 34
2a + b = 17

2a - b = 3    
2a + b = 17  +
4a = 20
a = 5

2a - b = 3    
2×5 - b = 3
-b = 3 - 10
-b = -7
b = 7

a + b = 7 + 5
          = 12